The Role of Myofascial Pain and Fibromyalgia on Pain and Disability of the Computer Users with Cumulative Trauma Disorders. Issue 3 (2nd October 2015) - Genc, Hakan; Tuncer, Özgül Bozkurt; Erdem, Hatice Rana; Nacır, Barış
Abstract: Objectives: We hypothesized that Cumulative Trauma Disorders (CTD) is common in computer workers and computer workers with CTD will have more FFS and MPS than those without. We further hypothesized that those with CTD and FS or MPS will have greater disability than those without. Methods: 170 computer users and 55 age, sex and body mass index matched healthy controls were included in the study. Pain assessment was made by visual analog scale. The presence of FS was evaluated using 2010 ACR classification criteria. The existence of MPS was evaluated using specific diagnostic criteria. In order to measure the general disability levels of the participants, Quick DASH Score (QDS) was used, besides to measure their disability levels during work, Quick DASH Work Score (QDWS) was used. Results: 114 (69%) of the computer users had CTD. The presence of MPS and FS in CTD group was significantly higher than the non-CTD group and controls ( p  < 0.001, p  < 0.001). QDS and QDWS were significantly higher in CTD group ( p  < 0.01– p  < 0.05). Statistically significant increases were found in pain score, QDS and QDWS in CTD group with FS and MPS ( p  < 0.05– p  < 0.001). Conclusions: We observed that CTD is common in computer users and determined that the existence of fibromyalgia and MPS are found to be serious risk factors for disability in computer users with CTD. We believe that treatment of FS and MPS have great importance in the treatment and more importantly in the prevention of this clinic entity which can cause serious pain, disability and workforce loss.